Evaluation of Ultrasound as an Imaging Modality in the Assessment of Carotid Artery Invasion in Patients with Head and Neck Cancer - Tijana Pandurović; Damir Štimac; Tajana Turk; Siniša Pešić; Vedran Zubčić; Matea Bogović; Nenad Čekić; Luka Šimić (Acta Clinica Croatica)
Tumor invasion of carotid arteries (CA) is found in 2%-7% of patients with head and neck cancer (HNC). There are no standardized criteria to evaluate the invasion. Tumor invasion of CA is assessed by using computerized tomography (CT) and magnetic resonance imaging. Ultrasound was also used but the method has not become daily routine. The aim of this study was to examine the effect of tumor invasion on CA dynamics and to evaluate the role of ultrasonography in the diagnosis of invasion. The study was conducted on two groups of 22 patients each. The first group consisted of patients with confirmed HNC and CA infiltration, while the second group consisted of patients without any data of HNC. Motion of the CA wall was assessed using ultrasound from which a CA was segmented and then the amount of motion was assessed by optical flow calculation. All patients with a CT-verified CA infiltration had an altered CA motion. The research showed that tumor-infiltrated CA had an altered dynamic when viewed on ultrasound.